Interhemispheric auditory connectivity: structure and function related to auditory verbal hallucinations - Steinmann, Saskia; Leicht, Gregor; Mulert, Christoph (Frontiers in Human Neuroscience, 2014)
Auditory verbal hallucinations (AVH) are one of the most common and most distressing symptoms of schizophrenia. Despite fundamental research, the underlying neurocognitive and neurobiological mechanisms are still a matter of debate. Previous studies suggested that “hearing voices” is associated with a number of factors including local deficits in the left auditory cortex and a disturbed connectivity of frontal and temporoparietal language-related areas. In addition, it is hypothesized that the interhemispheric pathways connecting right and left auditory cortices might be involved in the pathogenesis of AVH. Findings based on Diffusion-Tensor-Imaging (DTI) measurements revealed a remarkable interindividual variability in size and shape of the interhemispheric auditory pathways. Interestingly, schizophrenia patients suffering from AVH exhibited increased fractional anisotropy (FA) in the interhemispheric fibers than non-hallucinating patients. Thus, higher FA-values indicate an increased severity of AVH. Moreover, a dichotic listening (DL) task showed that the interindividual variability in the interhemispheric auditory pathways was reflected in the behavioral outcome: Stronger pathways supported a better information transfer and consequently improved speech perception. This detection indicates a specific structure-function relationship, which seems to be interindividually variable. This review focuses on recent findings concerning the structure-function relationship of the interhemispheric pathways in controls, hallucinating and non-hallucinating schizophrenia patients and concludes that changes in the structural and functional connectivity of auditory areas are involved in the pathophysiology of AVH.